Pembuatan Minuman Herbal Yang Berkhasiat Untuk Mengatasi Masalah Pencernaan (Detoks Tubuh) - Nurastuti Wulandari; Syahrul Syahrul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Herbal drinks have many health benefits such as strengthening the immune system, preventing diabetes, preventing cancer, relieving coughs and others. This community service was carried out on: Day/Date : Wednesday/09 November 2022 Time : 10.00 WITA - Done Ginger can fight Escherichia coli bacteria, Salmonella enteriditis, and Staphylococcusaureus, which can interfere with digestive problems. Then Lemongrass and turmeric are alternative medicines for stomach aches, stomach cramps, and other digestive problems. The main ingredients of the community service this time are ginger, lemongrass and turmeric, where the benefits of ginger are one of the spices that are widely known by the public. Fragrant lemongrass is used as a traditional medicine taken to treat sore throat, colitis, stomach ulcers, diarrhea, mouthwash, and stomach ache. And turmeric prevents heart disease, reduces pain in osteoarthritis sufferers, relieves itching of the skin, relieves menstrual disorders, overcomes digestive tract disorders, prevents cancer, reduces depression, overcomes skin problems. , and lemongrass so that it becomes a herbal drink, we received extraordinary enthusiasm from the public because they paid close attention while we explained the stages of its manufacture.